1984
DOI: 10.2105/ajph.74.10.1153
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated biphenyls: influence on birthweight and gestation.

Abstract: Fifty-one infants born to women employed at two capacitor manufacturing facilities with a history of high exposure to polychlorinated biphenyls (PCBs) had a mean birthweight of 153 grams less than that of 337 infants born to women who had worked in low-exposure areas (90 per cent confidence interval, -286 to -20 g); mean gestational age was 6.6 days shorter in the high-exposure infants (90 per cent CI, -10.3 to -2.9 days). After adjusting for gestational age, the difference in birthweight was markedly reduced,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
2

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(37 citation statements)
references
References 6 publications
2
32
1
2
Order By: Relevance
“…Similar effects have previously been reported for certain coplanar and ortho-substituted PCBs (Eriksson and Fredriksson 1996a, 1996bEriksson et al 1991). In addition, effects of prenatal and postnatal exposure to PCBs, such as lower gestational age and birth weight (Fein et al 1984;Rylander et al 2000;Taylor et al 1984), delayed development (Guo et al 1994), and intellectual impairment (Jacobson and Jacobson 1996), have been reported in humans.…”
supporting
confidence: 80%
“…Similar effects have previously been reported for certain coplanar and ortho-substituted PCBs (Eriksson and Fredriksson 1996a, 1996bEriksson et al 1991). In addition, effects of prenatal and postnatal exposure to PCBs, such as lower gestational age and birth weight (Fein et al 1984;Rylander et al 2000;Taylor et al 1984), delayed development (Guo et al 1994), and intellectual impairment (Jacobson and Jacobson 1996), have been reported in humans.…”
supporting
confidence: 80%
“…Our study showed that the rate of low birth weight infants (<2500 g) was 3-fold higher in the hotspot than in the unexposed region. Overall, our findings are in agreement with the report by Taylor et al (1984) on the number of risk factors for infants born with low birth weight. These authors also reported an increased rate of low birth weight infants and shortened gestational age among women who were occupationally exposed to toxic chemicals, such as TCDD or PCBs (Taylor et al 1989).…”
Section: Discussionsupporting
confidence: 93%
“…Produced in the United States until 1977 (Laden et al, 1999 ), PCBs are highly resistant to degradation, persist in animal and environmental reservoirs, and ascend the food chain, depositing in human tissues. Research suggests that PCB exposure in utero or during infancy is associated with lowered birth weight and gestational age Taylor et al, 1984 ), intellectual impairment (Jacobson and Jacobson, 1996 ), and delayed development (Guo et al, 1994 ) .…”
Section: Introductionmentioning
confidence: 99%